P1447Use of novel local impedance-based catheter in typical right atrial flutter ablation: preliminary data from a multicenter Italian study. (18th June 2020) - Ducceschi, V; Pandozi, C; Arestia, A; Rossi, L; Bencardino, G; Segreti, L; Schillaci, V; Auricchio, C; Aperuta, F; Malacrida, M; Sangiuolo, R
Abstract: Funding Acknowledgements: NO FUNDING Background: Many studies demonstrated the importance of an optimal tissue contact to obtain safe and effective lesions and to improve the clinical outcome in ablation of cavotricuspid isthmus (CTI) for typical right atrial flutter (AFL). Data about a novel technology able to measure local tissue impedance (LI) providing a measure of tissue characteristics and lesion formation is still lacking in right atrium or CTI working. Purpose: This analysis explores the relationship between LI measures and ablation spot lesion locations during ablation of CTI in common AFL patients (pts). Methods: Consecutive pts undergoing AFL ablation from the CHARISMA registry were included. A novel RF ablation catheter with dedicated algorithm (DirectSense - DS -) was used to measure LI at the distal electrode of this catheter. Each targeted spot was characterized in terms of LI parameters during RF delivery at the lateral, intermediate and posterior portions of the CTI. Successful single RF ablation was defined according with a reduction of voltage (RedV) by at least 50% or split in two separate potentials (SPL). Ablation endpoint was the creation of bidirectional conduction block across the isthmus. Results: A total of 135 ablation spot lesions were delivered in 20 pts (median 5 [3-11] lesions per pt): 7 (5%) at lateral, 88 (65%) at intermediate and 40 (30%) at posterior portions of the CTI. Acute success was obtained in all cases and no complications were observed. The median ablation time was 26 [17 – 36] seconds per lesion. 100 (74%) and 51 (38%) ablation spots were effective according with RedV or SPL, respectively. The mean LI was 106 ± 15Ω prior to ablation and 93 ± 13Ω after ablation (p < 0.0001, mean absolute LI drop 14 ± 7Ω, mean percentage LI drop 13%±6). Effective ablation spots showed a higher absolute impedance drop (15 ± 7Ω at effective RedV vs 9.6 ± 8Ω at ineffective RedV, p = 0.0001; 15.6 ± 7Ω at effective SPL vs 12.5 ± 7Ω at ineffective SPL, p = 0.0173) or % impedance drop (14%±6 at effective RedV vs 9%±7 at ineffective RedV, p < 0.0001; 14.5%±6 at effective SPL vs 11.6%±6 at ineffective SPL, p = 0.0103) compared with ineffective sites. No significant differences were found in terms of starting LI, ending LI or LI drop among CTI areas. The percentage of LI drop was associated both with RedV (odd ratio 1.17 (95%CI: 1.08 to 1.26, p = 0.0001)) and with SPL (odd ratio 1.08 (1.02 to 1.14, p = 0.0132)). Conclusion: In our preliminary experience, measured LI before and after RF delivery and LI drop appear to be consistent and homogeneous across different CTI ablation locations. The magnitude of the LI drop was associated with effective lesion formation and conduction block.